Mathematical Literacy Development by Integrated Teaching Method - Tayraukham, Assoc. Prof. Dr. Sombat; Jitkangwan, Kanjana; Rakapang, Wacharapong (Journal for Developing the Social and Community, 2016)
The scientific and technological progress of the modern world affected to sociocultural and economic change all country, these lead people must have knowledge up to changeable world, especially knowledge and skill of mathematical process which leads to be important tool for living. However, mathematical teaching in the current situation is not very successful because of teaching and learning is not consistent with current situation. Therefore, to develop the mathematical knowledge effectively need to use the integrated teaching method which consist of Content Integration, Method Integration